Problem-based numbered head together learning approach for a successful teaching strategy - Bayu Rima Aditya; Irawan Nurhas; Fathul Jannah (JINoP (Jurnal Inovasi Pembelajaran), 2022)
The study aims to investigate the potential of the Numbered Head Together (NHT) model for improving the learning engagement of elementary students in Indonesia. Although the work in this area is extensive, little is currently known about the adequacy and better strategy for implementing the model at the elementary school level. Classroom Action Research (CAR) was applied to this study, as it has been extensively used in elementary school teaching and is well established in the literature. The study results provide an extended approach as a proven successful process for applying the NHT model to elementary schools in Indonesia by incorporating the Problem Solving (PS) learning model into the NHT model. While this study was originally designed for the Indonesian context, we also see a possible application of the proposed expanded NHT model as transboundary for teaching activities in general at the elementary school level. This research serves as the first step toward a deeper insight into the practical application of the NHT and PS learning model in primary school contexts. The evaluation of the results provides initial evidence of the effectiveness of the combined model in improving student engagement in learning.